PERANCANGAN DASHBOARD UNTUK PELAYANAN SIRKULASI DI PERPUSTAKAAN UNIVERSITAS TARUMANAGARA - Danielo; Hugeng (Fakultas Teknologi Informasi Universitas Tarumanagara, 2023)
This journal writing is made with the following objectives, namely to designing the Circulation Services Dashboard at the Universitas Tarumanagara Library using Microsoft Power BI, monitoring the performance evaluation directly from 3 aspects of circulation services at the Universitas Tarumanagara (UNTAR) Library based on key performance indicator (KPI), and make it easier for library managers to read all circulation service transaction data based on the dashboard. By using literature study method and requirements prototype method, the dashboard design is displayed in the form of the bar chart using Microsoft Power BI. The design is divided based on 3 aspects, namely adding book titles, adding book copies, and book borrowing transactions. Based on the results of testing by the user on the Circulation Services Dashboard at the Universitas Tarumanagara Library, it can be concluded that the dashboard can display Year Filters, Month Filters, Science Field Filters, Book Title Addition Diagrams, Book Copy Addition Diagrams, Book Borrowing Transaction Diagrams, KPI Diagram for Adding Book Titles per Year, KPI Diagram for Adding Book Copies per Year, and KPI Diagram for Book Loan Transactions per Year properly and smoothly according to the user requests.